Isolated Bacteria from Hemodialysis Water Distribution Systems in Hemodialysis Centers in Bandung - bin Mohd Rafee, Mohd Hafeez; Sudigdoadi, Sunarjati; Dewanto, Julius B (Althea Medical Journal, 2016)
Background: Despite the advent of water treatment technology for the past few decades, bacterial contamination is still an everlasting issue that requires solid intervention. Many studies across the world have identified myriad of bacteria that colonize the hemodialysis water distribution system. This study was conducted to identify common bacteria that colonized the hemodialysis water distribution systems in Bandung.Methods: This was a descriptive laboratory study conducted at the Department of Microbiology Faculty of Medicine Universitas Padjadjaran in 2014. Sterile bottles were used to collect 16 samples of reverse osmosis water from 2 hemodialysis centers in Bandung. Approximately 15 ml of water volume was collected in each bottle from 7 standard points for water sampling in hemodialysis system. The samples were first inoculated into R2A agar by pour-plate method and colonies were subâcultured onto MacConkey and blood agar and the identification was based on Gram stain morphology, colony characteristics, and biochemical tests.Results: Micrococcus luteus and Pseudomonas sp. were the two predominant organisms which colonized the hemodialysis water distribution system. In addition, some genus of the Enterobacteriaceae such as Enterobacter aerogenes, Klebsiella pneumoniae, and Yersinia pseudotuberculosis were also isolated from the system and seemed to colonize the entire system.Conclusions: Bacterial contamination in hemodialysis water distribution system in Bandung is still a major problem regardless the efforts taken to minimize it. [AMJ.2016;3(2):259â64]Â DOI:Â 10.15850/amj.v3n2.788